Analisis Penggunaan Kandoushi yang Menyatakan Outou dalam Manga Detektif Conan Volume 98-99 - Tegar Rifqiaulian; Muhammad Ali Hamdi; Ruri Fadhillah Hakim (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2025)
In Japanese, interjections are known as kandoushi and are divided into kandou (impression), yobiake (call), outou (response), and aisatsugo (greeting). Kandoushi that express outou are kandoushi that express answers and responses to other people's speech. The reason for this research is based on the important role of kandoushi which expresses outou in everyday Japanese conversation. The purpose of this study is to describe the types and forms, usage, and meaning of kandoushi that express outou. The data source in this study is the Detective Conan manga Volume 98-99. The method used in this study is a qualitative descriptive method using a syntactic and semantic approach. The results of this study are that there are 3 types and 13 forms of kandoushi that express outou in the Detective Conan manga volume 98-99 with different usage and meaning. The frequency of occurrence of the types, uses, and meanings of kandoushi expressing outou in the Detective Conan manga volumes 98-99 reflects its use in everyday life.